(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The research aimed to identify the extent of family dialogue with sons and daughters in the university stage, and to know the method of dialogue used within the family from the point of view of university students, and the topics around which the family dialogue revolves, and whether the parents follow different methods of dialogue with their sons and daughters at the university stage; Where the research came in three sections, the first section included: the problem of the research; As for the second section included the theoretical framework of the research، as it dealt with the concept of family dialogue، the types of family dialogue and its importance for sons and daughters at the university level. The third section represented: the field framework of the research، which included the study of a sample of university students amounting to (81) male and female students; The research showed that there is a family dialogue with sons and daughters at the university level with a percentage of (92.6%) of the sample members، and that the sons and daughter’s academic achievement is the most topic of dialogue with a percentage of (61.7%) and the method of advice and guidance is the method used in dialogue with a percentage of (60.5%) and (77.8%) of the respondents reported a different style of dialogue with them when they became university students.